Neotype: Replace what is lost - Christensen, Tim (East Carolina University, 2023)
"Neotype: Replace what is lost" is a photographically based project aimed at exploring the intersection of Art and Science by using historical photographic techniques to celebrate and memorialize our insect partners. This thesis documents the development of the artist/scientist as he creates different bodies of work during his MFA. The final exhibition centers on the questions of how we know the world and creates a ritual that asks the observer to engage with insects as both objects of wonder and as creatures that are disappearing from our rapidly changing world.
Keywords: photography; tintype; alternative process; wet plate collodion; entomology; Insects in art; Endangered species in art; Science in art